Effect of adding different levels of soaked pigeon pea seeds (Cajanus cajan L) on the Growth and Feed Utilization Efficiency of Nile tilapia (Oreochromis niloticus) fingerlings. - Hassan M. Yagoub; Abdul Naser S. Ali; Rufida M. Mohammed; Mubarak M. Ali (International Journal of Aquaculture Research and Development, 2023)
This study was conducted to evaluate the effect of socked pigeon pea seed meal on Growth and Food Utilization Efficiency of Nile tilapia (Oreochromis niloticus) fingerlings. 120 fish the weight and length average (3.4±0.04g and 3.2±0.00cm) were randomly distributed in 12 plastic Tanks (Aquarium) 36L according to the complete randomization, allocated to a represent four treatments (T0, T1, T2, and T3) of Nile tilapia (Oreochromis niloticus) fingerlings. four feeds were prepared in pellet form which consisted of 0%, 25%, 50% and 75% pigeon pea seed meal as replacement of fish meal. All diets contents 30% protein. Nile tilapia (Oreochromis niloticus) fingerlings were fed at the rate of 5% of their body weight. The result showed significant variation (P < 0.05) in final body weight, weight gain (WG), daily weight growth (DWG), Specific Growth Rate (SGR), and Food Conversion Ratio (FCR) among treatments. But, high SGR in T0 (control) and the best FCR were obtained at T 0% pigeon pea seed meal. Over all, best growth performance was observed in fish fed diet T1 (25%). The best performing fish’s final weight, DWG, SGR and FCR were 9.46±0.33g, 0.13±0.01g/day, 2.93±0.73% /day and 1.49±0.30 respectively. On the other hand, there was high significant variation (P < 0.05) in survival rate were obtained at T2 (50%). this study recommend that a diet containing 25% Pigeon pea seed meal for juvenile Nile tilapia is optimum in terms of growth performance and profitability, and does not impact water quality and plankton abundance in plastic Tanks (Aquarium) culture system.
Keywords: Oreochromis niloticus